ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PERPUSTAKAAN DAERAH MALUKU UTARA (STUDI KASUS) - Rohani Katili; Nurlaila Nurlaila (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2013)
simultaneous from education variable and training, work satisfaction, comitmet, and work culture, to performance employee in Laibrary North Maluku Province. Data collecting Technique that used by using technique kuesioner was be next tested pass by validity test and reliabilitas. Sampling in research this is the employee in 4 laibrary in Propinsi North Province that is 75 responders. Analysis is conducted by using double reggression analysis.Research Result indicates that education variable and training, work satisfaction, comitment, and work culture in simultanneous have an effect ono significant to employee performance, nevertheless in partial that have significant influence to employees performance that is variable of work satisfaction, and work culture, whereas education variable and training, and comitment in significant has no inflence to performance labour laibrary in North Maluku Province.Keywords :